2021
DOI: 10.3390/ani11010096
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Dog Bite Incidents in Chile: Factors Related to the Patterns of Human-Dog Relationship

Abstract: Dog bites are one of the main public health problems. They produce important consequences for those who suffer them (physical and psychological injuries, secondary infections, sequelae, risk of transmission of zoonoses and surgeries, among others). The objective of this study was to characterize epidemiologically the incidents of bites in Chile and the patterns of human-dog relationship involved. The records analyzed in this article were obtained from bitten patients who attended the main public health facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
(71 reference statements)
2
5
1
Order By: Relevance
“…This pattern was reversed at older ages when females were affected in larger proportions. These results coincide with other studies like the one from Chile, which found that the highest frequency of dog bites for females was for the 40 and over age group (Barrios et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This pattern was reversed at older ages when females were affected in larger proportions. These results coincide with other studies like the one from Chile, which found that the highest frequency of dog bites for females was for the 40 and over age group (Barrios et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…France, the United States and Chile (Barrios et al, 2021;Overall & Love, 2001;Quirk, 2012;Rosado et al, 2009;Sarcey et al, 2017), the under 14 years of age group received most bites. The behaviour of children, lack of understanding of dogs' body language prior to the aggression and lack of adult supervision are some of the reasons that may explain the higher incidence of bites in this age group (Overall & Love, 2001;Quirk, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although Chile does not have canine rabies, a host of canine zoonoses [7,21,22] and dog bites [23] have had significant public health impacts. Dogs have also made their mark in online tourism blogs with a surprising number of articles, comments, and stories written by visitors to the country remarking on the astonishing number of dogs seen wandering every city of the country [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been carried out in order to understand the epidemiology of dog bites. Several authors have investigated the victim features, the characteristics of biting dogs and the context in which attacks occur [3,[8][9][10]. This led to the definition of a dog bite as a multifactorial phenomenon, whose expression is regulated by genetic, physiological, developmental, environmental and social factors [4].…”
Section: Introductionmentioning
confidence: 99%